PENGARUH BIMBINGAN KLASIKAL UNTUK MENINGKATKAN ADVERSITY QUOTIENT (DAYA JUANG) SISWA DI SMA NEGERI 1 TAMBANG - Nada Sahdu; Tri Umari; M. Arli Rusandi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Classical guidance is an assistance service for students that is given to a number of students with classical guidance service activities that are provided systematically, are preventive in nature and provide internal understanding and understanding of others that lead to learning, personal, career and social. This study aims to determine the effect of classical guidance to increase the adversity quotient (fighting power) of students at SMA Negeri 1 Tambang before and after being given services. This type of research is experimental research. This study used a one-group pretest-posttest design. The research subjects were 32 students of class XI IPA who had a low adversity quotient based on the adversity quotient scale measurement. This study uses the Wilcoxone test and the Spearman Rank test. For the analysis using SPSS Version 25. The results showed an increase, difference and influence of classical guidance in increasing the Adversity Quotient of students at SMAN 1 Tambang.Key Words: Influence, Classical Guidance, Adversity Quotient.